(3GdEfLjds
(3ChdgG (B:s
(3HSe GdCH hGdCHf hGdQhM GdbOS EdGg hGMO GdChdI ef MceI SdjeGf fahS GdUOjbjf ai jO Gddg hdf jdGeSge YPGH ESJTYQ ai EdMGX GdLgGd Cfge bO eGJhG s
(3BNQgG (B:s
(3hVY RfGQ GdbOjSI hGdOg EdG gfG GdcQje ai GdUfOhb GdebOS ai gjcdgG GdehbQ hGdSHM ddg OGFekG CHOkG s
(3cJHJ HYV GdYHGQGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdOjGfGJ GdCNQis